The Effectiveness of Developing the Mobile Application for Learning English for Academic Purposes in a Thai Regional University - Chaisuriya, Arnon; Rungsiri, Auemporn (Universitas Negeri Makassar, 2023)
The objectives of this research were to develop and test the efficiency of a mobile application for promoting out-of-class English practice for Thai university students enrolling in an English for academic purposes course. This mobile application featured interactive flashcards, multiple-choice quizzes, matching quizzes, spelling quizzes, and a news-update page. The participants in this study were 79 undergraduate students divided into two groups based on their voluntary use of the application. In the experimental group, after the pre-test, sixty-three students downloaded and used the application for one month, while the control group consisted of the 16 students who did not download or use the app after the pre-test. Both the pre-test and post-test consisted of listening, vocabulary, grammar, and reading. Their pre-test and post-test scores were compared by using the pair-sample t-test in the experimental group, and the Wilcoxon signed-rank test was used in the control group. Additional data regarding the usability and perceived effectiveness of the app were collected using an online questionnaire and analyzed using the mean and standard deviation. It was found that students who used the app performed significantly better in their post-test than in their pre-test, but that was not the case for students in the control group who did not use the app. The data from the questionnaire show that users were satisfied with the app features and frequently used the matching quizzes, usage quizzes, and meaning quizzes. They also agreed that the app was usable and effective, and they supported further development in terms of contents. This shows that the application should be implemented in order to increase achievement in learning English for specific purposes.